Early stage variable rate nitrogen fertilization of silage maize driven by multi-temporal clustering of archive satellite data. (1st June 2017) - Casa, R.; Pelosi, F.; Pascucci, S.; Fontana, F.; Castaldi, F.; Pignatti, S.; Pepe, M.
Abstract : Nitrogen fertilization of silage maize in Central Italy is typically carried out with two applications at early stages of crop development: 2 nd (V2) and 6 th (V6) leaf respectively. In such conditions, the crop has not yet fully covered the soil and proximal or remote sensing of the canopy is hindered by the strong soil background signal. There is thus great interest in rapid and inexpensive approaches to N fertilization prescription. Therefore, an indirect method for inferring information on yield potential and soil variability, through a field-based clustering of multi-temporal satellite data, has been developed using archive Landsat images to identify temporally constant patterns. This method is potentially useful for the creation of prescription maps. The usefulness of the method was evaluated during an N fertilisation field trial in Maccarese (Central Italy), in 2016. At the V2 stage, both uniform and variable rate applications were performed and compared. A pseudo-cross variogram and a standardized ordinary co-kriging methodology was used to highlight spatially variable significant differences among the treatments.